"Only the aprismo will save the Argentina". A reconstruction of the militancy Aprista In Argentina in the late 1930s - Sessa, Leandro (2010)
During the 1930’s in Argentina there were two Aprist organizations mainlyencouraged by Argentinean militants. These groups, though somewhat marginalin the political arena of Argentina, sought to build a political alternative in thatcountry inspired by the APRA. Some of the questions about the difficulties ofestablishing an «Argentinean Aprism» may be answered through the analysisof some characteristics of these organizations and the reconstruction of thepolitical and intellectual networks in which its members participated. And, atthe same time, the analysis produces new evidence related to APRA’s historyin Argentina, which until now had not been evaluated.